A more in-depth visualization for the heat transfer across the thermoluminescence detectors. (January 2022) - Sadek, A.M.
Abstract: An enhanced visualization model has been developed using the finite element method (FEM) to recover the flaw in the concept of the imperfect heat transfer in thermoluminescence (TL) detectors. The proposed model could provide more accurate measurements for the temperature lag between the heating element and the TL detector, as well as present a new viewpoint on how the heat transfers through the TL detector. The proposed model was used to calculate the temperature lag for various shapes of LiF detectors, and the results showed a significant difference when compared to the previous models. Furthermore, the analytical solutions, approximations, and assumptions proposed in the literature for solving the differential equation governing the temperature transfer across the TL detector have been reviewed with the advantage of the FEM. Highlights: The heat transfer across the TL detectors was simulated using the FEM. The analytical solutions of the heat transfer equation have been reviewed. A new conception for the imperfect heat transfer in TL detector has been proposed. The new approach allows for realistic simulations and accurate T L a g measurements.